Deficiency of the melanin biosynthesis genes SCD1 and THR1 affects sclerotial development and vegetative growth, but not pathogenicity, in Sclerotinia sclerotiorum. (30th January 2018) - Liang, Yue; Xiong, Wei; Steinkellner, Siegrid; Feng, Jie
Summary: The fungus Sclerotinia sclerotiorum is a necrotrophic plant pathogen causing significant damage on a broad range of crops. This fungus produces sclerotia that serve as the long‐term survival structures in the life cycle and the primary inoculum in the disease cycle. Melanin plays an important role in protecting mycelia and sclerotia from ultraviolet radiation and other adverse environmental conditions. In this study, two genes, SCD1 encoding a scytalone dehydratase and THR1 encoding a trihydroxynaphthalene reductase, were disrupted by target gene replacement, and their roles in mycelial growth, sclerotial development and fungal pathogenicity were investigated. Phylogenetic analyses indicated that the deduced amino acid sequences of SCD1 and THR1 were similar to the orthologues of Botrytis cinerea . Expression of SCD1 was at higher levels in sclerotia relative to mycelia. THR1 was expressed at similar levels in mycelia and sclerotia at early stages, but was up‐regulated in sclerotia at the maturation stage. Disruption of SCD1 or THR1 did not change the pathogenicity of the fungus, but resulted in slower radial growth, less biomass, wider angled hyphal branches, impaired sclerotial development and decreased resistance to ultraviolet light.